Pengaruh Model Pembelajaran Teams Games Tournament Berbantuan Media KOKAMI terhadap Motivasi Belajar Peserta Didik - Indah Saputri, Sonia; Syamsul, Syamsul; Safei, Safei (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to (1) describe the learning motivation of students with the learning model of teams games tournaments (TGT) assisted by mystery card box media (KOKAMI), (2) describe the learning motivation of students with conventional learning models, and (3) find out the influence of the TGT model assisted by the KOKAMI media on the learning motivation. With a non-equivalent control group design, this kind of research used a quasi-experimental design. The research population consisted of 240 students in class X SMA Negeri 2 Takalar. The sampling technique used was purposive sampling; the experimental class was X IPA 3, and the control class was X IPA 4, each consisting of 35 people. The research instrument used a questionnaire totaling 23 statement items and motivational observation sheets. Data analysis techniques included descriptive statistical analysis and inferential statistical analysis. The results showed that the learning motivation of students used the learning model of team games tournaments (TGT) assisted by mystery card box media (KOKAMI) in the high category. While the learning motivation of students using conventional learning models is in the medium category, there is an influence of the learning model of team games tournaments (TGT) assisted by mystery card box media (KOKAMI) on the learning motivation of class X students at SMA Negeri 2 Takalar.